COVID‐19 and Older Adults: What We Know. Issue 5 (20th April 2020) - Shahid, Zainab; Kalayanamitra, Ricci; McClafferty, Brendan; Kepko, Douglas; Ramgobin, Devyani; Patel, Ravi; Aggarwal, Chander Shekher; Vunnam, Ramarao; Sahu, Nitasa; Bhatt, Dhirisha; Jones, Kirk; Golamari, Reshma; et al.
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), a novel virus that causes COVID‐19 infection, has recently emerged and caused a deadly pandemic. Studies have shown that this virus causes worse outcomes and a higher mortality rate in older adults and those with comorbidities such as hypertension, cardiovascular disease, diabetes, chronic respiratory disease, and chronic kidney disease (CKD). A significant percentage of older American adults have these diseases, putting them at a higher risk of infection. Additionally, many adults with hypertension, diabetes, and CKD are placed on angiotensin‐converting enzyme (ACE) inhibitors and angiotensin II receptor blockers. Studies have shown that these medications upregulate the ACE‐2 receptor, the very receptor that the SARS‐CoV‐2 virus uses to enter host cells. Although it has been hypothesized that this may cause a further increased risk of infection, more studies on the role of these medications in COVID‐19 infections are necessary. In this review, we discuss the transmission, symptomatology, and mortality of COVID‐19 as they relate to older adults, and possible treatments that are currently under investigation. J Am Geriatr Soc 68:926–929, 2020